2017
DOI: 10.1088/1361-6641/aa7477
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a source-contacted light shield on the electrical characteristics of an LTPS TFT

Abstract: The electrical characteristics of a low-temperature polycrystalline silicon thin-film transistor (TFT) with a source-contacted light shield (SCLS) are observed and analyzed. Compared with that of a conventional TFT without a light shield (LS), the on-current of the TFT with an SCLS is lower because the SCLS blocks the fringing electric field from the drain to the active layer. Furthermore, the gate-to-source capacitance (C gs ) of the TFT with an SCLS in the off and saturation regions is higher than that of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Thus, research is required on processes that can significantly improve TFT electrical characteristics and reduce their environmental footprint. [24,25] In this regard, published research results have shown how device characteristics are improved by applying heat treatment to the surface after the deposition of a-IGZO as an active layer. [26][27][28][29][30] However, active layer materials exhibit different degradation processes in real environments, and identifying the degradation mechanisms in different environments might be unattainable.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, research is required on processes that can significantly improve TFT electrical characteristics and reduce their environmental footprint. [24,25] In this regard, published research results have shown how device characteristics are improved by applying heat treatment to the surface after the deposition of a-IGZO as an active layer. [26][27][28][29][30] However, active layer materials exhibit different degradation processes in real environments, and identifying the degradation mechanisms in different environments might be unattainable.…”
Section: Introductionmentioning
confidence: 99%